The difficulty index of biology topics in Indonesian Senior High School: Biology undergraduate students’ perspectives - Ahmad Fauzi; Alfin Miftachulia Rosyida; Miftachur Rohma; Diana Khoiroh (University of Muhammadiyah Malang, 2021)
Biology is a subject that contains of many difficult concepts to study. This study aimed to identify Biology topics taught in Senior High School (SHS) which were considered as difficult materials by undergraduate students. The data were gathered by means of a web-based survey from 198 Biology students of 25 universities and 51 Biology education students of nine universities in Indonesia. The biology students graduated from SHSs in 97 regions/municipality, while the biology education students were graduated from 34 regions/municipality. The data were analyzed using two formulas: 1) Biology Difficulty Index (BDI) to determine the difficulty index of Biology subject, and 2) Topic Difficulty Index (TDI) to examine the difficulty index of each Biology topics. The results showed that the highest value of TDI was Genetics. There was no significant difference of BDI between Biology students and Biology education students. The lower of the students’ BDI, the higher the level of their interest in Biology subject. The primary cause of difficulty encountered by the students in studying various topics of Biology was the complicated characteristics of the materials. The findings of this study can be followed up by designing diagnostic tests and instructional designs in biology topics which consider students’ difficulty.